Magyar írók József főherceg emlékezete nyomában - Kovács Anita; A Nagy Háború hatása a mindennapok kultúrájának változására (2015) (Szeged) (2018)
Archduke Joseph Karl was popular not only among the gypsies, but also he did significant activities in the Hungarian culture and public education. This essay pointed out Hungarian activities of his through with the correspondence of Mór Jókai. The connection of the archduke and Jókai was romantice friendship. They respected each other, and Jókai was almost family member. Jókai (and other hungarian writers too) didn’t write about Hungarian Habsburg, he didn’t appareled hungarian elements (as hungarian writers were in case of Rudolf crownprince) he handled him as a Hungarian man. It didn’t evolved around him suchlike cult, than for example Rudolf crownprince or Elizabeth queen, preferably placed to get anecdotes and different stories.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Nyelvek és irodalom